MATH INSTRUCTIONAL MEDIA DESIGN USING COMPUTER FOR COMPLETION OF TWO-VARIABLES LINEAR EQUATION SYSTEM BY ELIMINATION METHOD* - Nurbaiti Nurbaiti; Salmawaty Salmawaty; Muhammad Subianto; Reza Wafdan (Universitas Syiah Kuala, 2017)
Abstract. Science and technology have been rapidly evolved in some fields of knowledge, including mathematics. Such development can contribute to improvements on the learning process that encourage students and teachers to enhance their abilities and performances. In delivering the material on the linear equation system with two variables (SPLDV), the conventional teaching method where teachers become the center of the learning process is still well-practiced. This method would cause the students get bored and have difficulties to understand the concepts they are learning. Therefore, in order to the learning of SPLDV easy, an interesting, interactive media that the students and teachers can apply is necessary. This media is designed using GUI MATLAB and named as students’ electronic worksheets (e-LKS). This program is intended to help students in finding and understanding the SPLDV concepts more easily. This program is also expected to improve students’ motivation and creativity in learning the material. Based on the test using the System Usability Scale (SUS), the design of interactive mathematics learning media of the linear equation system with Two Variables (SPLDV) gets grade B (excellent), meaning that this learning media is proper to be used for Junior High School students of grade VIII.Keyword: SPLDV, Learning Media, Students’ Electronic Worksheet (e-LKS) *Judul ini telah dipresentasikan pada Seminar Nasional: Indonesian Students Conference on Science and Mathematics(ISCSM) 11-12 November 2015, Banda Aceh Indonesia